Environmental mediation: The mediation procedure on the waste management plan in the district of Neuss, North Rhine-Westphalia - Initial results of the companion social science research - Hans-Joachim Fietkau; Helmut Weidner (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1995)
For the first time ever in the Federal Republic of Germany a mediation procedure on a waste management concept has been carried out. It took place in Neuss in the German federal state of North Rhine-Westphalia. The interdisciplinary project group, Environmental Mediation, from the Science Centre Berlin for Social Research (WZB) was one of the initiators of the mediation project. It conducted social science research that accompanied the procedure throughout. The procedure began in March 1992 and ended in August 1993 with a controversial compromise; in particular, it proved impossible to reach agreement on the question of whether waste incineration was objectively necessary and legally required. The results presented here should be seen as a workshop report; the final report is planned for winter 1995. This paper will provide an overview of events leading up to the mediation procedure and the course it has taken, in conjunction with the methodological approach of the parallel empirical research and the international comparative studies that are still going on. It will then report some of the central findings from our participatory observation and questionnaire survey, and examine the influence of the normal political process before, during and after the mediation procedure. The problem of success and failure as criteria for assessing the results of the mediation will be discussed. The conclusion drawn is that, although the mediation procedure in Neuss did not manage to counter the gravitational force of the normal political process, certain aspects indicating a positive conflict resolution have emerged as well as results that are not normally possible to achieve in formal (conventional) procedures. – – Zum ersten Mal wurde in der Bundesrepublik Deutschland ein Mediationsverfahren zu einem Abfallwirtschaftskonzept durchgeführt. Es fand im Kreiss Neuss (NRW) statt und ist von der interdisziplinären WZB-Projektgruppe Media-tionsverfahren im Umweltschutz mit initiiert und sozialwissenschaftlich begleitet worden. Das Verfahren begann im März 1992 und endete im August 1993 mit einem strittigen Kompromiß: insbesondere über die Frage, ob eine Müllverbrennungsanlage sachlich notwendig und rechtlich erforderlich sei, konnte keine Einigung erzielt werden. Bei den hier vorgetragenen Ergebnissen handelt es sich um einen Werkstattbericht, der Endbericht wird Ende 1994 unter dem Titel Umweltverhandeln im Verlag edition sigma, Berlin, erscheinen. In diesem Beitrag wird - neben einem Überblick zur Vorgeschichte und zum Ablauf des Mediationsverfahrens, zum methodischen Vorgehen der empirischen Begleitforschung sowie zu den noch laufenden internationalen Vergleichsstudien - über einige zentrale Befunde aus der teilnehmenden Beobachtung und der Fragebogenerhebungen sowie zum Einfluß des politischen Nornalprozesses vor, während und nach dem Mediationsverfahren berichtet. Erfolg und Mißerfolg als Kriterien zur Bewertung von Mediationsergebnissen werden problematisiert. Fazit ist, daß durch das Neusser Mediationsverfahren die Gravitationskräfte des politischen Normalprozesses nicht aufgehoben werden konnten, sich aber Formen und Ergebnisse einer positiven Konfliktregelung ergeben haben, die in förmlichen Regelungsverfahren üblicherweise nicht erreichbar sind.
Keywords: 300; Abfallentsorgung; Umweltpolitik; Verhandlungen; Neuss (Kreis)